The Politics of Law on Corruption Eradication - Kristiono, Natal; Astuti, Indri (Law Research Review Quarterly, 2018)
Corruption is a deviant behavior to obtain some things that are socially and / or legally prohibited. All forms of government are prone to corruption in practice. Corruption in politics and bureaucracy can be trivial or severe, organized or not. Corrupt behavior that afflicts almost all political elites has undermined aspects of national and state life, this is a scourge for the general public who thinks that politics justifies any means. The burden of political costs borne by a candidate is very high, even above the fairness rate. The average cost to run for a district or city legislative member is around 150 million to 500 million to be able to occupy a seat in the legislature. These costs include party registration, pre-campaign costs, campaign costs to other costs, including advertising in mass media both electronic and print. This high burden causes legislative candidates to seek sources of funds from all walks of life, which results in them sometimes having campaign finance debts. Even if there is aid, it is usually binding, which at a time will curb legislative candidates if they become members of the council later. While salary and allowance income while serving as a member of the council is not sufficient to pay off debt, this then affects their performance and is caught in the vortex of abuse of power and corruption.